PENGARUH AKUPRESUR TUI NA TERHADAP BERAT BADAN ANAK BALITA USIA 24 - 59 BULAN DIWILAYAH KERJA UPT PUSKESMAS PAMBANG KABUPATEN BENGKALIS PROVINSI RIAU TAHUN 2022 - Suharsanto Suharsanto; Tri Krianto Karjoso; Heryudarini Harahap; Novita Rany; Jasrida Yunita (Ensiklopedia of Journal, 2023)
Weight gain is one indicator of children health aged 24-59 months which can be used as a benchmark for growth of underfive aged children. Decreased appetite in children is one of the causes of weight problems, this can be overcome by giving stimulation. One of the recommended stimulation is Tui Na Acupressure. The study objective was to determine the effect of Tui Na Acupressure on the weight of children under five children aged 24–59 months. The study was carried out at UPT Puskemas Pambang in July-August 2022. The study was quantitative with a quasi-experimental design and a two-group design with pretest-posttest. A total sample of 100 children were grouped into 50 children for the experimental group and 50 children for the control group.  The sampling method was purposive. Tui Na acupressure was carried out for 24 days in the experimental group, while the control group was not given the intervention. Tui Na acupressure was conducted at the Puskesmas and sample houses by trained health workers. Children's weight were collected before and after the intervention was given. Statistical test using non parametric test. The results of this study showed a significant increase in body weight (p<0.05) both in the experimental group and the control group at the end of the study. There was a significant difference in the mean weight gain (p<0.000) between the group given Tui Na Acupressure (0.3±1.3 Kg) and the control group (0.1±0.21 Kg). The conclusion of this study was that there was a higher weight gain of underfive children when Tui Na acupressure was given. It is recommended that underfive children aged 24-59 months should acquire Tui Na Acupressure to support optimal growth and development.